Necessity "-->" and sufficiency "<---".
The statement we want to prove:
mn is odd if and only if m and n are odd.
Necessity "-->"
Assume mn is odd. {We want to prove m and n are odd}.
We can prove this by contradiction. Assume that it is NOT the case that m and n are odd. That means we have the following three cases:
Case I: m is even, n is even. Then
m = 2i, n = 2j for some integers i and j.
mn = (2i)(2j)
mn = 4ij
mn = 2(ij), and clearly mn is even. This is a contradiction for this case.
Case 2: m is odd, n is even. Then
m = 2i + 1, n = 2j, and
mn = (2i + 1)(2j)
mn = 4ij + 2j
mn = 2(2ij + j), showing that mn is even. We've obtained another partial contradiction.
Case 3: m is even, n is odd. (Since multiplication is commutative, the proof is similar to case 2 that mn is also even).
Therefore, if both m and n are NOT odd, mn is even; this is a contradiction. It therefore follows that m and n are odd.
Sufficiency. "<---"
Assume m and n are both odd. Then
m = 2i + 1
n = 2j + 1
mn = (2i + 1)(2j + 1)
mn = 4ij + 2i + 2j + 1
mn = 2(2ij + i + j) + 1, showing mn is an odd number.
Therefore, since necessity and sufficiency has been proven, it follows that
mn is odd if and only if m and n are odd.
2007-03-07 05:18:57
·
answer #1
·
answered by Puggy 7
·
1⤊
0⤋
What if one of them is even?
For instance m=2k for an integer k:
mn = 2k*n=(k * n) + (k * n)
That's even!
If OTOH both are odd m=2k+1 n=2p+1
mn = (2k + 1)(2p + 1) = 4kp + 2p + 2k + 1 = 2(2kp +p + k) + 1
A number greater by 1 than an even number is odd.
2007-03-07 13:14:13
·
answer #2
·
answered by Amit Y 5
·
1⤊
0⤋
The only way to get an odd number for a multiplication answer is to have both factors be odd.
even times even yields even
odd times even yields even
even times odd yields even
ODD times ODD yields ODD
2007-03-07 13:11:30
·
answer #3
·
answered by Maverick 7
·
0⤊
1⤋